The influence of workplace environment on employee work performance among automotive engineers: A preliminary study - Abiddin, Norhasni Zainal (Edelweiss Applied Science and Technology, 2024)
In organizations, the high performance of work has become more critical thing and workplace play a crucial part in giving engineers their job behaviors and attitude towards their performances. But in automotive, a sector renowned for its tight deadlines and stressful working conditions that often drive engineers to despair, an environment promoting collaboration, communication and ongoing learning, enabling engineers to better negotiate shifts impacting the industry like autonomous vehicles and emissions standards. It offers them the best chance of handling these republishing expectations and performing at their highest level. This pilot study intended to explore the impact of workplace attributes on work performance among automotive engineers in Klang Valley, Malaysia. Of these, 19 are automotive companies from which target respondents will be engineering employees who each represent a critical sector of the industry and should therefore be highly relevant to the research objectives. Different type of descriptive and inferential statistical methods has been used to analysis the data which is relevant for the research objective. This relationship is important for organisations who want to have their engineering staffs as productive as possible and for individuals who are trying to advance in a very competitive work environment. By conducting this preliminary study, it is hoped that overall comprehension of workplace dynamics in the automotive industry will continue to improve and strategies developed to maximise employee performance will enhance sustainability and ultimately, competitiveness of this local and global industry.